Asian Communication : Research, Training, Planning - Hawaii Univ., Honolulu. East-West Center; Lerner, Daniel; Hawaii Univ., Honolulu. East-West Center (Washington, D.C. : Distributed by ERIC Clearinghouse, 1976)
A selection of eight papers on Asian communication is presented for the purpose of alerting communication researchers to significant work being done outside of the academic community. Topics include (1) a Malaysian experience in using commercial resources for audience research, (2) a content analysis model of the Pakistani press, (3) the provincial press and national development in Malaysia and the Philippines, (4) a comparative analysis of the mass communications systems of Burma, Malaysia, and Thailand, (5) teaching and training in building the Asian Communications Network, (6) national planning and telecommunications in the Asia/Pacific context, (7) economics of communication technology, and (8) Asian contexts for development communication. (CMV)
Microfiche.
Keywords: Asian Studies; Case Studies; Comparative Analysis; Developing Nations; Economic Factors; Information Networks; International Studies; Mass Media; News Media; Program Development; Teaching Models; Telecommunications; Burma -- Malaysia, Thailand -- Pakistan -- Philippines; Reports, Research